Rare earth ion-doped lithium iron phosphate positive electrode material and preparation method thereof

By doping rare earth ions and combining with functional carbon sources, a lithium iron phosphate cathode material with a double carbon coating layer was prepared, which solved the problem of insufficient electrochemical performance of LiFePO4 and achieved higher conductivity and lithium ion diffusion ability. , improving the cycle performance and stability of the battery.

CN119361647APending Publication Date: 2025-01-24HUNAN YUNENG NEW ENERGY BATTERY MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411513111.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The electrochemical performance of LiFePO4, the positive electrode material of the existing lithium-ion battery, is affected by its own structure, and the ion mobility is relatively low, which affects its circulation capacity and the battery's magnification charge and discharge performance.

Method used

By doping rare earth ions and combining with a functional carbon source, a lithium iron phosphate cathode material with a double carbon coating layer was prepared. The doping of rare earth ions introduces lattice defects and improves conductivity; the carbon wrapping layer formed by the functional carbon source further reduces the resistivity and enhances the diffusion ability of lithium ions.

Benefits of technology

Improve the electrical conductivity of lithium iron phosphate and the diffusion capacity of lithium ions, enhance the cycle performance and stability of the battery, and improve the electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a rare earth ion-doped lithium iron phosphate positive electrode material and a preparation method thereof, and relates to the technical field of lithium ion batteries, the preparation method comprises the following steps: adding L FeyX (1-y) PO4 and a part of functional carbon source into deionized water together, carrying out ultrasonic oscillation for 1 hour, then carrying out suction filtration and drying, sintering the dried mixture in a nitrogen atmosphere at 720 DEG C for 6 hours, and carrying out vacuum drying to obtain the rare earth ion-doped lithium iron phosphate positive electrode material. Cooling to room temperature and grinding to obtain a lithium iron phosphate positive electrode material precursor; and adding the lithium iron phosphate positive electrode material precursor and the residual functional carbon source into deionized water, carrying out ultrasonic oscillation for 2 hours, carrying out suction filtration, drying, sintering the dried mixture in a nitrogen atmosphere at 450 DEG C for 3 hours, heating to 780 DEG C, sintering for 5 hours, cooling to room temperature, and grinding to obtain the lithium iron phosphate positive electrode material. By doping rare earth ions in lithium iron phosphate and adding sodium phosphate in a carbon source, the electrochemical performance of the lithium iron phosphate positive electrode material can be enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a rare earth ion-doped lithium iron phosphate positive electrode material and a preparation method thereof. Background Art

[0002] Lithium-ion batteries have become an ideal power source for modern digital electronic products due to their advantages such as high operating voltage, high energy density, low self-discharge rate, stability and environmental protection. With the continuous expansion of its application fields, especially with the rapid development of new energy vehicles and UPS power storage industries, the demand for lithium-ion batteries has increased dramatically. However, the cost and performance of lithium-ion batteries are mainly affected by their positive electrode materials, so it is particularly important to develop low-cost, environmentally friendly, high specific energy and high cycle characteristics positive electrode materials.

[0003] At present, the main cathode materials used in lithium-ion batteries include LiCoO2, LiNiO2 and LiMn2O4. However, these materials have disadvantages such as resource shortage, high price, high toxicity, difficulty in preparation and safety issues, which limit their widespread application. As a new type of lithium-ion battery cathode material, LiFePO4 has attracted much attention due to its abundant resource reserves, low price, stable structure, good safety performance, non-toxicity and environmental friendliness. The theoretical capacity of LiFePO4 is 170mAh / g, and the operating voltage is 3.4V (vs Li / Li + ) is lower than the decomposition voltage of most electrolytes, and has good cycle performance and thermal stability, especially at high temperatures, and has a good cycle life, making it the most widely used positive electrode material for lithium-ion batteries.

[0004] However, the LiFePO4 cathode material is affected by its own structure, and its ion mobility is low, which in turn affects its cycle capacity and the rate charge and discharge performance of the battery. In order to improve the electrochemical performance of LiFePO4, researchers have conducted a large number of modification studies, including doping with conductive carbon or coating carbon on the surface of lithium iron phosphate particles, metal coating, metal ion doping and particle size control. Although these methods have improved the electrochemical performance of LiFePO4 to a certain extent, they still have limitations. Therefore, how to further improve its electrochemical performance is still a technical problem that needs to be solved urgently. Summary of the invention

[0005] The purpose of the present invention is to provide a rare earth ion doped lithium iron phosphate positive electrode material and a preparation method thereof, to solve the following technical problems:

[0006] How to improve the electrochemical performance of lithium iron phosphate positive electrode materials.

[0007] The purpose of the present invention can be achieved through the following technical solutions:

[0008] The invention discloses a rare earth ion-doped lithium iron phosphate positive electrode material, comprising the following components in parts by weight: 95-100 parts of modified lithium iron phosphate, 6-8 parts of a functional carbon source;

[0009] Preferably, the modified lithium iron phosphate is 98 parts and the functional carbon source is 7 parts.

[0010] The chemical formula of the modified lithium iron phosphate is LiFe y X (1-y) PO4, wherein X is a rare earth element, 0.96≤y≤0.99; preferably, y=0.98.

[0011] Furthermore, the LiFe y X (1-y) The preparation method of PO4 is:

[0012] According to LiFe y X (1-y) The lithium source, iron source, X source and phosphorus source are weighed and ground respectively, and then added into deionized water to form a mixed solution with a solid content of about 30%. The mixture is stirred evenly under argon protection, and then ethylene glycol in an amount greater than the volume of the mixed solution is added. The mixture is magnetically stirred at 200°C for 3 hours. The addition of ethylene glycol can reduce the degree of agglomeration of the raw materials during the hydrothermal process, which is beneficial to improving the crystallinity of the material. Finally, the obtained slurry is centrifuged, dried and ground to obtain LiFe y X (1-y) PO4.

[0013] Furthermore, the lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium acetate, lithium phosphate, and lithium dihydrogen phosphate; preferably, the lithium source is lithium carbonate.

[0014] Furthermore, the iron source includes one or more of iron oxides (FeO, Fe2O3, Fe3O4), iron salts (FeCl3, Fe2(SO4)3, Fe(NO3)3), and preferably, the iron source is FeCl3.

[0015] Further, the X source includes one or more of rare earth oxides, rare earth hydroxides, and rare earth salts (rare earth nitrates, rare earth sulfates, rare earth carbonates, rare earth oxalates, and rare earth phosphates); X is a combination of any one or more of lanthanum, cerium, praseodymium, neodymium, promethium, samarium, and europium; preferably, X is lanthanum, and the X source is lanthanum oxide (La2O3).

[0016] Furthermore, the phosphorus source includes one or more of phosphoric acid, ammonium phosphate, and diammonium phosphate; preferably, the phosphorus source is phosphoric acid.

[0017] When rare earth ions in the X source are doped into lithium iron phosphate, lattice defects will be caused in the material. These defects can serve as channels for electron conduction, reducing resistivity and thus improving the conductivity of the material. At the same time, the particle size of the material will be smaller, shortening the diffusion path of lithium ions. Moreover, the radius of rare earth ions is larger than that of iron ions. After doping, the unit cell parameters and volume of the material will increase, which is also conducive to the diffusion of lithium ions. Doping with rare earth ions can also stabilize the structure of lithium iron phosphate, reduce volume changes during the cycle, and help maintain the integrity of the material, thereby improving the cycle performance and stability of the battery.

[0018] Furthermore, the preparation method of the functional carbon source is: mixing and grinding the composite carbon source and sodium phosphate in a mass ratio of (7-9):1, adding them to deionized water and stirring them evenly to form a mixture, and granulating the mixture by a spray dryer to obtain a uniform powdery functional carbon source;

[0019] Preferably, the mass ratio of the composite carbon source to sodium phosphate is 8:1.

[0020] A small amount of sodium phosphate in the functional carbon source shuttles through the carbon layer to form an irregular ultra-thin film layer. When the battery is working, it can reduce the decomposition of the electrolyte and absorb water in the electrolyte, thereby reducing the level of hydrofluoric acid or even removing hydrofluoric acid, thereby protecting the active substances of the battery from side reactions with the electrolyte during the charge and discharge process, thereby maintaining the structural integrity of the electrode material and improving its electrochemical performance.

[0021] Furthermore, the composite carbon source includes glucose, sucrose and polyvinyl alcohol in a mass ratio of 5:2:1.

[0022] In a second aspect, the present invention further discloses a rare earth ion-doped lithium iron phosphate positive electrode material as described below, characterized in that it comprises the following steps:

[0023] S1: LiFe y X (1-y) PO4 and part of the functional carbon source are added to deionized water, ultrasonically vibrated for 1 hour, filtered, dried at 120-140°C for 4-5 hours, and the dried mixture is sintered at 720°C for 6 hours in a nitrogen atmosphere, cooled to room temperature, and ground to obtain a lithium iron phosphate positive electrode material precursor with a carbon coating layer;

[0024] S2: Add the lithium iron phosphate cathode material precursor and the remaining functional carbon source into deionized water, and filter after ultrasonic vibration for 2 hours, and dry at 120-140°C for 4-5 hours. The dried mixture is sintered at 450°C for 3 hours in a nitrogen atmosphere, and then heated to 780°C for 5 hours. After cooling to room temperature, grind to obtain a lithium iron phosphate cathode material with a double-layer carbon coating layer;

[0025] The mass ratio of the functional carbon source added in step S1 to step S2 is (9-15):6.

[0026] During the preparation process, the functional carbon source forms a carbon coating layer in two steps. The carbon coating layer formed for the first time is carbon-coated again. During this process, the external carbon source provides new nuclei for crystal growth during the sintering process. New crystals grow on its surface to form a dense external carbon coating layer. The internal carbon coating layer has insufficient contact with the external carbon source, so fewer new crystal structures are generated. The structural distribution of the new crystals is relatively loose, forming a network-like carbon structure connected between the two carbon coating layers, which is beneficial to the migration and conduction of electrons, thereby improving the conductivity to a certain extent.

[0027] Further, in step S1, LiFe y X (1-y) When PO4 and some functional carbon sources are added to deionized water, LiFe y X (1-y) The total solid content of PO4 and part of the functional carbon source is 40-50%; preferably, the solid content is 45%.

[0028] Furthermore, in step S2, when the lithium iron phosphate cathode material precursor and the remaining functional carbon source are added into deionized water together, the total solid content of the lithium iron phosphate cathode material precursor and the remaining functional carbon source is 50-60%; preferably, the solid content is 55%.

[0029] Beneficial effects of the present invention:

[0030] 1. In the lithium iron phosphate positive electrode material doped with rare earth ions of the present invention, after the rare earth ions in the X source are doped into the lithium iron phosphate, lattice defects inside the material will be caused. These defects can serve as channels for electron conduction, reduce the resistivity, and thus improve the conductivity of the material; at the same time, the particle size of the material is also reduced, so that the diffusion path of the lithium ions becomes shorter; and the radius of the rare earth ions is larger than that of the iron ions, and the unit cell parameters and volume of the material after doping will increase, which is also conducive to the diffusion of lithium ions; the doping of rare earth ions can also stabilize the structure of the lithium iron phosphate, reduce the volume change during the cycle, and help maintain the integrity of the material, thereby improving the cycle performance and stability of the battery.

[0031] 2. In the rare earth ion-doped lithium iron phosphate positive electrode material of the present invention, a small amount of sodium phosphate in the functional carbon source shuttles through the carbon layer to form an irregular ultra-thin film layer. When the battery is working, it can reduce the decomposition of the electrolyte and absorb water in the electrolyte, thereby reducing the level of hydrofluoric acid or even removing the hydrofluoric acid, thereby protecting the active substances of the battery from side reactions with the electrolyte during the charge and discharge process, thereby maintaining the structural integrity of the electrode material and improving its electrochemical performance.

[0032] 3. In the rare earth ion-doped lithium iron phosphate positive electrode material of the present invention, the functional carbon source forms a carbon coating layer in two steps, and carbon coating is performed again on the outside of the first formed carbon coating layer. In this process, the external carbon source provides new nuclei for crystal growth during the sintering process, and new crystals grow on its surface to form a dense external carbon coating layer. However, the internal carbon coating layer has insufficient contact with the external carbon source, so less new crystal structure is generated, and the structural distribution of the new crystal is relatively loose, which will form a network-like carbon structure connected between the two carbon coating layers, which is beneficial to the migration and conduction of electrons, thereby improving the conductivity to a certain extent. DETAILED DESCRIPTION

[0033] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] The experimental methods in the following examples, unless otherwise specified, are all conventional methods, and are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial channels.

[0035] Preparation Example 1

[0036] Preparation of modified lithium iron phosphate (LiFe 0.98 La 0.02 PO4).

[0037] Lithium carbonate (Li2CO3), ferric chloride (FeCl3), lanthanum oxide (La2O3), and phosphoric acid (H3PO4) were weighed in a molar mass ratio of 50:98:1:100 and were respectively placed in a ball mill for grinding for 2 hours, and then transferred to a stirring tank, and a proper amount of deionized water was added to the stirring tank to form a mixed solution with a solid content of about 30%, and stirred at 500 rpm for 3 hours under argon protection, and then ethylene glycol exceeding the volume of the mixed solution was added, and magnetic stirring was performed at 200°C for 3 hours. Finally, the obtained slurry was transferred to a centrifuge for centrifugation, taken out and placed in a vacuum drying oven for drying at 120°C for 4 hours, and finally added to a grinder for dry grinding to obtain LiFe 0.98 La 0.02 PO4.

[0038] Preparation Example 2

[0039] Preparation of modified lithium iron phosphate (LiFe 0.98 Pr 0.02 PO4).

[0040] Compared with Preparation Example 1, the only difference is that the lanthanum oxide with a molar mass ratio of 1 is replaced by praseodymium nitrate (Pr(NO3)3·6H2O) with a molar mass ratio of 2, and other conditions remain the same, and finally LiFe 0.98 Pr 0.02 PO4.

[0041] Preparation Example 3

[0042] Preparation of modified lithium iron phosphate (LiFe 0.98 Eu 0.02 PO4).

[0043] Compared with Preparation Example 1, the only difference is that the lanthanum oxide with a molar mass ratio of 1 is replaced by europium nitrate (Eu(NO3)3·6H2O) with a molar mass ratio of 2, and other conditions remain the same, and finally LiFe 0.98 Eu 0.02 PO4.

[0044] Preparation Comparative Example 1

[0045] Preparation of lithium iron phosphate (LiFePO4)

[0046] Lithium carbonate (Li2CO3), ferric chloride (FeCl3), and phosphoric acid (H3PO4) were weighed in a molar mass ratio of 1:2:2 and were respectively placed in a ball mill and ground for 2 hours. The mixture was then transferred to a stirring tank, and an appropriate amount of deionized water was added to the stirring tank to form a mixed solution with a solid content of approximately 30%. The mixture was stirred at 500 rpm for 3 hours under argon protection, and ethylene glycol in an amount exceeding the volume of the mixed solution was added. The mixture was magnetically stirred at 200°C for 3 hours. Finally, the obtained slurry was transferred to a centrifuge for centrifugation, taken out, and dried in a vacuum drying oven at 120°C for 4 hours. Finally, the slurry was added to a grinder for dry grinding to obtain LiFePO4.

[0047] Preparation Example 4

[0048] Preparation of functional carbon source.

[0049] 50 g of glucose, 20 g of sucrose, 10 g of polyvinyl alcohol and 10 g of sodium phosphate were mixed and ground, added into an ultrasonic mixer containing 100 g of deionized water and ultrasonically mixed for 2 h to form a mixture, and the mixture was granulated by a spray dryer to obtain a uniform powdery functional carbon source.

[0050] Preparation Comparative Example 2

[0051] Preparation of carbon source.

[0052] Compared with Preparation Example 4, the only difference is that sodium phosphate is not added, and other conditions remain the same, and finally a carbon source is obtained.

[0053] Example 1

[0054] Preparation of rare earth ion-doped lithium iron phosphate positive electrode material.

[0055] Step 1: 95g of LiFe prepared in Preparation Example 1 0.98 La 0.02 PO4 and 4 g of the functional carbon source prepared in Preparation Example 4 were added to an ultrasonic stirrer filled with 100 g of deionized water for ultrasonic vibration for 1 h, and then transferred to a suction filter for suction filtration. The slurry obtained after suction filtration was placed in a vacuum drying oven and dried at 120 ° C for 5 h. The dried mixture was transferred to a sintering furnace and sintered at 720 ° C for 6 h under a nitrogen atmosphere. After cooling to room temperature, it was added to a grinder for dry grinding to obtain a lithium iron phosphate positive electrode material precursor with a carbon coating layer;

[0056] Step 2: Add the lithium iron phosphate cathode material precursor obtained in step 1 and 2 g of functional carbon source into an ultrasonic stirrer filled with 95 g of deionized water for ultrasonic oscillation for 2 hours, and then transfer it to a suction filter for suction filtration. The slurry obtained after filtration is placed in a vacuum drying oven and dried at 120°C for 5 hours. The dried mixture is transferred to a sintering furnace and sintered at 450°C for 3 hours under a nitrogen atmosphere, and then heated to 780°C for sintering for 5 hours. After cooling to room temperature, it is added to a grinder for dry grinding to obtain a lithium iron phosphate cathode material having a double-layer carbon coating and doped with rare earth ions.

[0057] Example 2

[0058] Preparation of rare earth ion-doped lithium iron phosphate positive electrode material.

[0059] Step 1: 98g of LiFe prepared in Preparation Example 1 0.98 La 0.02 PO4 and 5g of the functional carbon source prepared in Preparation Example 4 were added to an ultrasonic stirrer filled with 110g of deionized water for ultrasonic vibration for 1h, and then transferred to a suction filter for suction filtration. The slurry obtained after suction filtration was placed in a vacuum drying oven and dried at 130°C for 4.5h. The dried mixture was transferred to a sintering furnace and sintered at 720°C for 6h under a nitrogen atmosphere. After cooling to room temperature, it was added to a grinder for dry grinding to obtain a lithium iron phosphate positive electrode material precursor with a carbon coating layer;

[0060] Step 2: Add the lithium iron phosphate cathode material precursor obtained in step 1 and 2 g of functional carbon source into an ultrasonic stirrer filled with 95 g of deionized water for ultrasonic oscillation for 2 hours, and then transfer it to a suction filter for filtration. The slurry obtained after filtration is placed in a vacuum drying oven and dried at 130°C for 4.5 hours. The dried mixture is transferred to a sintering furnace and sintered at 450°C for 3 hours under a nitrogen atmosphere, then heated to 780°C and sintered for 5 hours. After cooling to room temperature, it is added to a grinder for dry grinding to obtain a lithium iron phosphate cathode material having a double-layer carbon coating and doped with rare earth ions.

[0061] Example 3

[0062] Preparation of rare earth ion-doped lithium iron phosphate positive electrode material.

[0063] Step 1: 100g of LiFe prepared in Preparation Example 1 0.98 La 0.02 PO4 and 5g of the functional carbon source prepared in Preparation Example 4 were added to an ultrasonic stirrer filled with 110g of deionized water for ultrasonic vibration for 1h, and then transferred to a suction filter for suction filtration. The slurry obtained after suction filtration was placed in a vacuum drying oven and dried at 140°C for 4h. The dried mixture was transferred to a sintering furnace and sintered at 720°C for 6h under a nitrogen atmosphere. After cooling to room temperature, it was added to a grinder for dry grinding to obtain a lithium iron phosphate positive electrode material precursor with a carbon coating layer;

[0064] Step 2: Add the lithium iron phosphate cathode material precursor obtained in step 1 and 3 g of functional carbon source into an ultrasonic stirrer filled with 100 g of deionized water for ultrasonic oscillation for 2 hours, then transfer it to a suction filter for filtration, and place the slurry obtained after filtration in a vacuum drying oven and dry it at 140°C for 4 hours. The dried mixture is transferred to a sintering furnace, sintered at 450°C for 3 hours in a nitrogen atmosphere, and then heated to 780°C for 5 hours. After cooling to room temperature, it is added to a grinder for dry grinding to obtain a lithium iron phosphate cathode material having a double-layer carbon coating and doped with rare earth ions.

[0065] Example 4

[0066] Preparation of rare earth ion-doped lithium iron phosphate positive electrode material.

[0067] Compared with Example 2, the only difference is that the LiFe prepared in Preparation Example 1 in step 1 0.98 La 0.02 PO4 was replaced by LiFe prepared in Preparation Example 2 0.98 Pr 0.02 PO4, and other conditions remain the same, and finally a lithium iron phosphate positive electrode material with a double-layer carbon coating and doped with rare earth ions is obtained.

[0068] Example 5

[0069] Preparation of rare earth ion-doped lithium iron phosphate positive electrode material.

[0070] Compared with Example 2, the only difference is that the LiFe prepared in Preparation Example 1 in step 1 0.98 La 0.02 PO4 was replaced by LiFe prepared in Preparation Example 3 0.98 Eu 0.02 PO4, and other conditions remain the same, and finally a lithium iron phosphate positive electrode material with a double-layer carbon coating and doped with rare earth ions is obtained.

[0071] Comparative Example 1

[0072] Compared with Example 2, the only difference is that the LiFe prepared in Preparation Example 1 in step 1 0.98 La 0.02 PO4 was replaced by LiFePO4 obtained in Comparative Preparation Example 1, and other conditions remained the same, and finally a lithium iron phosphate positive electrode material with a double-layer carbon coating was obtained.

[0073] Comparative Example 2

[0074] Compared with Example 2, the only difference is that the functional carbon source prepared in Preparation Example 4 in step one is replaced by the carbon source prepared in Comparative Preparation Example 2, and other conditions remain the same, and finally a lithium iron phosphate positive electrode material with a double-layer carbon coating layer is obtained.

[0075] Comparative Example 3

[0076] 98g of LiFe prepared in Preparation Example 1 0.98 La 0.02 PO4 and 7g of the functional carbon source prepared in Preparation Example 4 were added together into an ultrasonic stirrer filled with 110g of deionized water and ultrasonically vibrated for 1h, and then transferred to a suction filter for filtration. The slurry obtained after filtration was placed in a vacuum drying oven and dried at 130°C for 4.5h. The dried mixture was transferred into a sintering furnace and sintered at 720°C for 6h under a nitrogen atmosphere. After cooling to room temperature, it was added to a grinder for dry grinding to obtain a lithium iron phosphate positive electrode material with a carbon coating layer.

[0077] The lithium iron phosphate positive electrode materials obtained in Examples 1-5 and Comparative Examples 1-3 were respectively made into batteries for testing of electrochemical properties. The preparation method was as follows: 90g of lithium iron phosphate positive electrode material, 5g of Super-P, and 5g of polyvinylidene fluoride were mixed evenly, and then 200g of N-methylpyrrolidone solvent was added and mixed evenly to obtain a black slurry. The aluminum foil was placed in a coating machine, and the black slurry was poured in. After uniform coating, the slurry was transferred to an oven and dried at 40°C for 4h. The dried aluminum foil was then placed in a punching machine, and several pole pieces containing active substances were punched out and weighed. The pole pieces were placed in a drying bottle, and the pole pieces were transferred to a vacuum drying oven and dried at 110°C for 6h. Finally, the button batteries were assembled in a vacuum glove box.

[0078] Then, the prepared button battery was subjected to electrochemical performance tests, the charge transfer resistance was tested using an electrochemical workstation, and the capacity retention rate was tested using a constant current-constant voltage charge-discharge method, and the test results are listed in Table 1, which is as follows:

[0079] Table 1

[0080]

[0081] By analyzing the data in Table 1, it can be known that the rare earth ion doped lithium iron phosphate positive electrode material prepared in Examples 1-5 has a significantly lower charge transfer resistance than the lithium iron phosphate positive electrode material prepared in Comparative Examples 1-3, which indicates that its electron migration rate is faster, while the capacity is significantly higher, which indicates that its rate performance is better; based on this, it can be known that the lithium iron phosphate positive electrode material having a double-layer carbon coating layer and doped with rare earth ions of the present invention has stronger electrochemical properties.

[0082] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.

Claims

1. A rare earth ion-doped lithium iron phosphate positive electrode material, characterized in that: The invention comprises the following components in parts by weight: 95-100 parts of modified lithium iron phosphate and 6-8 parts of functional carbon source; The chemical formula of the modified lithium iron phosphate is LiFe y X (1-y) PO4, where X is a rare earth element, 0.96≤y≤0.99; The functional carbon source is a composition of a composite carbon source and sodium phosphate.

2. The rare earth ion-doped lithium iron phosphate positive electrode material according to claim 1, characterized in that: The raw materials for preparing the LiFeyX(1-y)PO4 include a lithium source, an iron source, an X source, and a phosphorus source, wherein X is a combination of any one or more of lanthanum, cerium, praseodymium, neodymium, promethium, samarium, and europium.

3. The rare earth ion-doped lithium iron phosphate positive electrode material according to claim 2, characterized in that: The lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium acetate, lithium phosphate, and lithium dihydrogen phosphate; The iron source includes one or more of iron oxides and iron salts; The X source includes one or more of rare earth oxides, rare earth hydroxides, and rare earth salts; The phosphorus source includes one or more of phosphoric acid, ammonium phosphate, and diammonium phosphate.

4. The rare earth ion-doped lithium iron phosphate positive electrode material according to claim 1, characterized in that: The LiFe y X (1-y) The preparation method of PO4 is: According to Li Fe y X (1-y) The lithium source, iron source, X source and phosphorus source were weighed and ground respectively, and then added into deionized water, stirred evenly under argon protection, and then ethylene glycol was added, stirred at 200 ° C for 3 h, and the obtained slurry was centrifuged, dried and ground to obtain Li Fe y X (1-y) PO4.

5. The rare earth ion-doped lithium iron phosphate positive electrode material according to claim 1, characterized in that: The composite carbon source comprises glucose, sucrose and polyvinyl alcohol in a mass ratio of 5:2:

1.

6. The rare earth ion-doped lithium iron phosphate positive electrode material according to claim 5, characterized in that: The preparation method of the functional carbon source is as follows: a composite carbon source and sodium phosphate having a mass ratio of (7-9):1 are mixed and ground, then added into deionized water and stirred evenly to form a mixture, and the mixture is granulated by a spray dryer to obtain a uniform powdery functional carbon source.

7. A rare earth ion-doped lithium iron phosphate positive electrode material according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1: Li Fe y X (1-y) PO4 and part of the functional carbon source were added to deionized water, and then filtered and dried after ultrasonic vibration for 1 hour. The dried mixture was sintered at 720°C for 6 hours in a nitrogen atmosphere, cooled to room temperature and ground to obtain a lithium iron phosphate positive electrode material precursor; S2: adding the lithium iron phosphate cathode material precursor and the remaining functional carbon source into deionized water, and then filtering and drying after ultrasonic vibration for 2 hours. The dried mixture is sintered at 450°C for 3 hours in a nitrogen atmosphere, and then heated to 780°C for 5 hours. After cooling to room temperature, it is ground to obtain a lithium iron phosphate cathode material; The added mass ratio of the functional carbon source in step S1 and step S2 is (9-15):

6.

8. The rare earth ion-doped lithium iron phosphate positive electrode material according to claim 7, characterized in that: In step S1, LiFe y X (1-y) When PO4 and some functional carbon sources are added to deionized water, Li Fe y X (1-y) The total solid content of PO4 and part of the functional carbon source is 40-50%.

9. The rare earth ion-doped lithium iron phosphate positive electrode material according to claim 7, characterized in that: In step S2, when the lithium iron phosphate cathode material precursor and the remaining functional carbon source are added into deionized water together, the total solid content of the lithium iron phosphate cathode material precursor and the remaining functional carbon source is 50-60%.

10. The rare earth ion-doped lithium iron phosphate positive electrode material according to claim 7, characterized in that: In step S1 and step S2, the drying temperature is 120-140° C. and the drying time is 4-5 hours.